A new karstic cave-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from Northern Vietnam - van Tri, Ngo; Onn, Chan Kin (Zootaxa, 2011)
A new species of bent-toed gecko, Cyrtodactylus cucphuongensis sp. nov. is described from the karst forest of Cuc Phuong National Park, Ninh Binh province, Northern Vietnam. It differs from all other species of Indo-Chinese Cyrtodactylus by the following combination of characters: SVL 96.0 mm; absence of precloacal and femoral pores; 19 subdigital lamellae on first toe, 24 on fourth toe; large, dark spots on top of head; wide, prominent nuchal band; and five or six dark, irregular, broad bands between limb insertions.